1985
DOI: 10.1063/1.334821
|View full text |Cite
|
Sign up to set email alerts
|

Concentration dependence of UV and electron-excited Tb3+ luminescence in Y3Al5O12

Abstract: The emission spectrum of Tb3+ substituted in YAG to various concentrations (x in Y3−xTbxAl5O12 ranges from 3×10−5 to 3×10−1) has been measured on samples prepared by two different methods. These methods are powder preparation by coprecipitation and growth of crystalline layers by liquid-phase epitaxy. The spectrum consists of two groups of lines, one group around 550 nm originating from the 5D4 level and one group around 450 nm from the 5D3 level. The intensity of the two groups of lines depends on the method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
57
1
3

Year Published

1989
1989
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(75 citation statements)
references
References 14 publications
14
57
1
3
Order By: Relevance
“…2(b)). The ratio of the total integrated intensity from the 'De level to that of the 5D3 level is about 3, which is the same value as reported for Y,Al,O,,:Tb [28]. For the sample containing 5% terbium, these 5D3 -+ 7FJ emissions are no longer observed due to cross-relaxation between Tb3+ ions.…”
Section: [=Isupporting
confidence: 69%
“…2(b)). The ratio of the total integrated intensity from the 'De level to that of the 5D3 level is about 3, which is the same value as reported for Y,Al,O,,:Tb [28]. For the sample containing 5% terbium, these 5D3 -+ 7FJ emissions are no longer observed due to cross-relaxation between Tb3+ ions.…”
Section: [=Isupporting
confidence: 69%
“…24 The dependence of the branch ratio on the Tb concentration has been extensively studied and is well-explained with the cross-relaxation theory. 22,25 This dependence can be used as intrinsic evidence of the phase formation and uniform doping. The quantitative agreement indicates that the designed materials are synthesized successfully, and the parallel SC microreactions can be applied to a combinatorial study of high-temperature materials.…”
Section: Resultsmentioning
confidence: 99%
“…Kang et al [41] reported that the particle size, shape, crystallinity, defects etc significantly affects the luminescence characteristics of YAG:Tb 3+ . Whereas, Van der Weg et al [42] studied the effect of doping concentration on the luminescence behavior of YAG:Tb 3+ . They observed that at low doping concentrations, primarily the absorption of excitation wavelength affects the luminescence characteristics without having any direct effect of the process of cross relaxation favoring emission from 5 D 3 state, whereas, at higher concentration the cross relaxation process favors the emission from 5 D 4 state.…”
Section: Characterization Of Preparedmentioning
confidence: 99%